Concepção de mediação com tecnologias digitais de informação e comunicação na formação de professores de matemática - Silva, Idelma Izabel de Camargo (2021)
Over the past few years, there has been an expansive technological advance, which ended up impacting various sectors of society, such as Education. In view of this, the present investigation aims to identify and understand the conceptual and instrumental aspects linked to teaching practice in a mathematics teacher training course at a Instituto Federal de Goiás (IFG), Goiânia. Thus, the central question that guides this investigation is the following: "What is the concept of technological education adopted by teachers who work in teacher training courses in mathematics? In order to substantiate the discussions carried out, the theoretical postulates of Vygotsky (1984) and Davydov (1988) on pedagogical mediation were used, a central concept in the construction of the most contextualized and meaningful pedagogical practice, both for the teacher and for the student. In addition, with the investigative purpose of understanding the didactic-methodological implications of the use of Digital Information and Communication Technologies (DICTs) in the classroom, it was based on the postulates of Sancho e Hernández (2006), Peixoto (2016) and Cysneiros (1998). As for the research methodology, it is configured as a quali-quantitative case study, since the data collected are expressed in numerical form, but always analyzed and evaluated in the light of the theoretical contribution, in an interpretative approach. The data collection took place through the application of a structured questionnaire for teachers of the Institute, working in higher education and teachers of the Mathematics discipline. Finally, it was found that the uses of DICTs dynamize the teaching-learning process, provided it is used properly, which requires planning, study and continuous reflection on the part of teachers